A new hardware efficient stream cipher based on hash functions. (4th August 2009) - Deepthi, P.P.; Sathidevi, P.S.; Lakshmi, V.S.
The design of a new hardware efficient stream cipher based on hash functions and its analysis are presented in this paper. Since the output keystream is a hashed version of the secret key, the security of the cipher directly depends on the one-wayness of the hash function. With the advance of wireless communication technology, mobile communications has become more convenient than ever. However, due to the openness of wireless communication, it is difficult to protect the privacy between communicating parties. Since stream ciphers are less expensive in hardware, they are widely used for confidentiality in wireless sensor networks, WEP and GSM networks. Hash functions are generally employed in ad-hoc networks for integrity verification and authentication of data and control packets. Most of the available hash function based stream ciphers are optimised for software efficiency. So a stream cipher that has least hardware complexity, less power consumption and high security gains importance in these days.